KOSMOLOGI DALAM PANDANGAN IMAM KHOMEINI - Muhammad Alfan Sidik, (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2022)
The harmony between humans and the universe is getting less due to overexploitation. To overcome this, the proper guidance on treating the universe properly is highly needed. Therefore, Alquran has invited humans to take care of and be concerned about natural sustainability. This study focuses on the cosmology of Imam Khomeini regarding the universe since he is one of the most significant figures in the Iran revolution, known as a statesman, Sufi, philosopher, and Theologian. This study employs a qualitative approach using a literature review of Imam Khomeini’s publications. Anchored in Tajalli and Wahdatul would proposed by Ibnu ‘Arabi and other cosmology theories from philosophers and theologians, the cosmology of Khomeini was analyzed critically. The study reveals that the universe is the name of Allah, the name is the sign, and all creatures in the world are the sign of Allah. This leads to the perspective that the universe is Tajalli. From this point of view, humans should treat the universe more appropriately since it is a medium to make them get closer to their god.